ANALISIS RENDEMEN MINYAK DAN INTI KELAPA SAWIT PADA PKS BERKAPASITAS 30 TON/JAM - HUTASUHUT, MHD FUAD MAHRUZ WIRA'I; Situmeang, Pirmana; Sinaga, Shiva Anggreini; Namudany, Rania; Al-Khoir, Habib; Siregar , Ajis Paroji; Raja, Pada Mulia; Purwanto, Heri; Saragih, Sri Wahyuna; Fachrizal (Jurnal Agro Fabrica, 2025)
The palm oil industry plays a vital role in the Indonesian economy, with palm oil (CPO) and palm kernel (PKO) yields as indicators of processing efficiency. This study aims to analyze the yield of CPO and PKO at 30 ton/hour PKS through a quantitative approach with field methods and laboratory tests. Raw and boiled Fresh Fruit Bunch (FFB) samples were taken from 30 ton/hour PKS in Langkat Regency, North Sumatra, then analyzed using material balance, moisture content, oil extraction (soxhletation), and kernel separation. The results showed that the average CPO yield on raw FFB was higher (32.12%) than that on boiled FFB (23.94%), while the PKO yield on boiled FFB (7.74%) was superior to that on raw FFB (3.84%). Factors such as fruit maturity, sterilization process, and extraction efficiency have a significant effect on yield. The findings recommend optimizing the quality of raw materials and processing processes to increase productivity. This study provides a scientific basis for mill in performance evaluation and yield improvement strategies